The Pine Branch, April 1932 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1932)
This periodical contains several pieces written by various members of the Writer's Club. There are several short stories, poems, and an editorial on the freshmen experience. Additionally there are a number of advertisements from local Valdosta businesses at the end of the publication.
Outlook -- "These Charming People" -- The Organ tells an Old Story -- My Lady of the Rocking-horse Days -- Youth's Disappointment -- Cats Among Men -- Song -- Analogy -- Fatal Encounter -- L'Heaure Bleue -- Editorial -- Critical Tips -- Locals -- Clubs -- Y.W.C.A. -- Societies -- Athletics -- Alumnae -- Jokes -- "He"
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education